Two-year Outcome of Quality of Life and Health Status for the Elderly with Chronic Limb-threatening Ischemia - Peters CML (Dove Medical Press, 2020)
Chloé ML Peters,1 Paul Lodder,2,3 Jolanda de Vries,2,4 Stijn L Steunenberg,1 Eelco J Veen,1 Hans GW de Groot,1 Gwan H Ho,1 Lijckle van der Laan1,5 1Department of Surgery, Amphia Hospital, Breda, The Netherlands; 2Department of Medical and Clinical Psychology, Tilburg University, Tilburg, The Netherlands; 3Department of Methodology and Statistics, Tilburg University, Tilburg, The Netherlands; 4Department of Medical Psychology, Elisabeth-TweeSteden Hospital Tilburg University, Tilburg, The Netherlands; 5Department of Cardiovascular Science, UZ Leuven - University Hospitals, Leuven, BelgiumCorrespondence: Lijckle van der LaanAmphia Hospital, Molengracht 21, Breda, CK 4818, the NetherlandsTel +31 76 595 5000Email lvanderlaan@amphia.nlPurpose: In elderly patients with chronic limb-threatening ischemia (CLTI), there is little scientific understanding of the long-term changes of quality of life (QoL) and health status (HS) after treatment. The primary goal of this study was to provide long-term QoL and HS results for elderly CLTI patients after therapy. Treatments consisted of endovascular revascularization, surgical revascularization, or conservative treatment. Furthermore, the aim of this study was to identify the distinctive trajectories of QoL and HS.Patients and Methods: CLTI patients aged ≥ 70 years were included in a prospective observational cohort study with a two-year follow-up. The WHOQOL-BREF was used to asses QoL. The 12-Item Short Form Health Survey was used to measure HS. The QoL and HS scores were compared to the scores in the general elderly Dutch population. Latent class trajectory analysis was used.Results: A total of 195 patients were included in this study. After two years, in all treatment groups patients showed significantly higher physical QoL score compared to baseline and there was no significant difference with the corresponding values in the elderly Dutch population. In the latent class trajectory analysis, there were no overlapping risk factors for poorer QoL or HS.Conclusion: This study shows that QoL levels in surviving elderly CLTI patients in the long-term do not differ from the corresponding values for elderly in the general population. There were no disparities in sociodemographic, clinical and treatment characteristics associated with poorer QoL and HS. This study was carried out to encourage further analysis of the influence of biopsychosocial characteristics on QoL and HS in elderly CLTI patients.Keywords: quality of life, health status, peripheral arterial disease, frail elderly, chronic limb-threatening ischemia